Hyper swollen perfluorinated smectic liquid crystal by perfluorinated oils. Issue 1 (1st December 2014) - Murase, Masatsugu; Takanishi, Yoichi; Nishiyama, Isa; Yoshizawa, Atsushi; Yamamoto, Jun
Abstract : We studied the hyper-swollen behavior of a perfluorinated smectic liquid crystal, 11-(4′-cyanobiphenyl-4-yloxy)undecyl pentadecafluorooctanoate (BI), through addition of perfluorinated oils. Abstract : We studied the hyper-swollen behavior of a perfluorinated smectic liquid crystal, 11-(4′-cyanobiphenyl-4-yloxy)undecyl pentadecafluorooctanoate (BI), through addition of perfluorinated oils. The studied compound, BI, has a bilayer SmA–SmC phase sequence due to microphase separation of hydrocarbon chains and perfluorinated chains. We found that BI can be diluted with straight-chain, soft perfluorinated oils and that the repeat distance of the smectic layer can be greatly swollen to about three times thicker than that of pure BI. However, there was no clear physical mechanism for the long-range interlayer repulsive forces, such as the electrostatic force, observed in the lyotropic system. Furthermore, we found that interlayer tilting can be propagated along the smectic layers in the SmC phase even in the hyper-swollen state, despite insertion of thick liquid layers of perfluorinated oil between the smectic layers of BI. The orientation of the intercalated perfluorinated oils was also discussed based on the conoscope observation.